TP53 Gene Polymorphisms in Cancer Risk: The Modulating Effect of Ageing, Ethnicity and TP53 Somatic Abnormalities - Denisov, Evgeny V.; Cherdyntseva, Nadezhda V.; Litviakov, Nicolay V.; Malinovskaya, Elena A.; Babyshkina, Natalya N.; Belyavskaya, Valentina A.; Voevoda, Mikhail I. (IntechOpen, 2012)
None